Kehidupan Sosial Ekonomi Buruh PT Sumatera Tropical Spices di Kenagarian Sungai Buluh Kabupaten Padang Pariaman Tahun 1993-2020 - Amirah Amani; Etmi Hardi (PAMA Aksara, 2021)
This study examines the Socio-Economic Life of Workers of PT Sumatra Tropical Spices in Kenagarian Sungai Buluh, Padang Pariaman Regency 1993-2020. This study aims to explain how the changes and development of socio-economic life and the level of welfare of the workers of PT Sumatra Tropical Spices. This study uses historical methods, which include heuristics, source criticism, analysis, synthesis, and interpretation as well as historiography (historical writing). The results of this study indicate that the socio-economic life of workers at PT Sumatra Tropical Spices from 1993-2020 has increased. The initial changes in socio-economic life were seen after 1998 and slowly increased in the following years. Workers of PT Sumatra Tropical Spices work from 08.00-17.00 WIB, with that they get income in the form of salaries, production bonuses, THR, health facilities, and pension benefits. With a steady income, some of them already have private homes, are able to own two-wheeled vehicles (motorcycles), washing machines, televisions, and other electronic devices, as well as the education of the workers' children who are able to send them to college.